Impact of Physician's Education on Adherence to Tuberculosis Treatment for Patients of Low Socioeconomic Status in Bangladesh - Lee, Shinwon; Khan, Omar Faruk; Seo, Jeong Ho; Kim, Dong Yeon; Park, Kyung-Hwa; Jung, Sook-In; Chung, Eun-Kyung; Jang, Hee-Chang (Chonnam medical journal, 2013)
Successful tuberculosis control depends on good adherence to treatment. Yet, limited data are available on the efficacy of methods for improving the adherence of patients of low socioeconomic status. We evaluated the impact of physician-provided patient education on adherence to anti-tuberculosis medication in a low socioeconomic status and resource-limited setting. A pre-/post-intervention study was conducted at a suburban primary health care clinic in Bangladesh where an intensive education strategy was established in May 2006. Treatment outcomes of tuberculosis patients from March 2005 to April 2006 (pre-intervention) and from May 2006 to December 2007 (post-intervention) were compared. Among 354 patients, 198 (56%) were treated before intervention and 156 (44%) were treated after intervention. Cumulative adherence to anti-tuberculosis medication was significantly greater in the intervention group than in the control group in univariate and multivariate analyses. Physician's education can contribute to increasing the adherence of patients in resource-limited settings.